The Correlation between Counsellor Competence in Multicultural Counselling and the Application of Cultural Values in the School Environment among Junior High School Students - Syaninda Putri Asyifa Siregar; Diana Septi Purnama; Najla Husna; Uswatun Hasanah Sitompul (Yayasan Keluarga Guru Mandiri, 2024)
Counselor competence in applying and implementing multicultural counseling is an essential aspect because students come from different cultural, ethnic, religious, and linguistic backgrounds. Competent counselors will be able to understand and appreciate these differences to provide services that are more effective and sensitive to each client's unique needs. This study aims to determine the relationship between multicultural counselor competence and implementing cultural values in schools. This study used a correlational design involving 82 students as samples, selected through a proportional random sampling technique. Data were collected using the multicultural counselor competence scale and cultural values scale. The data analysis technique used was Pearson Product Moment correlation. The results show a positive relationship between multicultural counselor competence and the application of cultural values at school. That is, the higher the level of counselor competence in multicultural counseling, the higher the level of application of cultural values at school. This finding can be the basis for guidance and counseling teachers to further improve their competence, especially in multicultural counseling, so applying cultural values in a school can also be carried out optimally because guidance and counseling teachers participate and contribute generously.